2021
DOI: 10.1093/ntr/ntab131
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use Among 1 310 716 Women of Reproductive age (15–49 Years) in 42 Low- and Middle-Income Countries: Secondary Data Analysis From the 2010-2016 Demographic and Health Surveys

Abstract: Introduction Tobacco use among women, especially during pregnancy is a public health concern. There is a need to understand the diverse nature of their tobacco consumption across the globe. Methods We used Demographic and Health Surveys (DHS) data collected between 2010 and 2016 from 42 low- and middle-income countries (LMICs) to estimate the prevalence of smoking, smokeless tobacco, and dual use among pregnant and non-pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 28 publications
3
23
0
1
Order By: Relevance
“…It suggests that tobacco use among women during postpartum is higher than during pregnancy in LMICs. 3 , 5 Much higher prevalence estimates of tobacco during pregnancy have been reported from population-based studies in high-income countries, including the USA (6.7%) 18 and the UK (10.6%). 19 The highest prevalence of tobacco use among breastfeeding women was in the Southeast Asia region, while the lowest was in the European region.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It suggests that tobacco use among women during postpartum is higher than during pregnancy in LMICs. 3 , 5 Much higher prevalence estimates of tobacco during pregnancy have been reported from population-based studies in high-income countries, including the USA (6.7%) 18 and the UK (10.6%). 19 The highest prevalence of tobacco use among breastfeeding women was in the Southeast Asia region, while the lowest was in the European region.…”
Section: Discussionmentioning
confidence: 98%
“…In another study using DHS data for 42 LMICs for 2010-2016, the prevalence of smoking and smokeless tobacco use among non-pregnant women was estimated at 1.1% (95% CI 0.8–1.4) and 0.8% (0.4–1.4), respectively. 5 Studies report that many women quit tobacco during pregnancy, but a large proportion resume during the postpartum period, often to the level of their preconception tobacco use, 6 however stoppage of tobacco use during pregnancy in LMICs is not universal.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests a need to raise awareness about early attempts at cigarette smoking and the need for developing intervention programs to reduce the early initiation of tobacco use in girls from a low level of national economic development. Unfortunately, the prevalence of cigarette smoking has increased along with increasing country income among girls aged 13–15 years [ 22 ] and women aged 15–49 years [ 42 ]. This indicates major issues in reducing the high prevalence of cigarette smoking in high-income countries and highlights how to prevent the early initiation of cigarette smoking in low-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…A recent secondary data analysis by Shukla et al (2021) on tobacco use by women showed concerning numbers regarding the prevalence of ST during pregnancy, especially in South-east Asia Region. Since the period from conception up to two years of age in children, i.e., the first 1000 days of life provide a critical stage of development and linear growth, external factors can influence the health conditions of both mother and developing fetus ( Quelhas et al, 2018 ).…”
Section: Effects On Pregnancy Outcomesmentioning
confidence: 99%